Whispering gallery mode emission from photonic microtubes - DONEGAN, JOHN FRANCIS; GOUNKO, IOURI; PEROVA, TANIA; RAKOVICH, YURY (IEEE, 2006)
We have found cylindrical glass microtubes can be formed by vacuum assisted filtration using a micro-channel glass matrix followed by thermal treatment of the material. The microtubes are strongly luminescent and exhibit sharp whispering gallery modes. The ease of fabrication suggest that such photonic structures will find use as both microsensors and microlasers
International Conference on Transparent Optical Networks, 8th: 2006
ICTON 2006
PUBLISHED
Keywords: microtubes; whispering gallery modes; photonic structures,; microlasers